LEIGH SYNDROME: A CASE REPORT WITH A MITOCHONDRIAL DNA MUTATION - Lopes, T. (2018)
Objective: Leigh syndrome is a neurodegenerative disorder with an incidence of 1:40,000 live births. It presents wide clinical, biochemical, and genetic heterogeneity, but with homogenous neuropatoradiological alterations. There is no specific treatment, and the prognosis is reserved. This case report aimed familiarize health professionals with the disease. Case Description: A 16-month-hold girl who was followed in outpatient clinic due to axial hypotonia and delayed psychomotor development. Karyotype, auditory evoked potentials and ophthalmologic evaluation were normal. Evidence of hyperlactacidemia and hypocitrullinemia was detected in the patient. After performing brain magnetic resonance under anesthesia, hypotonia got worse, and the patient was hospitalized after an episode of cyanosis and apnea. The electroencephalogram showed no epileptiform activity. Neuroimaging revealed bilateral lenticular hyperintensity, especially in the putamen and in the left globus pallidus regions. Molecular analysis revealed an 8993T>G (MT-ATP6) mutation in the mitochondrial DNA. Comments: Between 10 and 30% of individuals with Leigh syndrome have mitochondrial DNA mutations. The decompensation after anesthetic intercurrences is typically associated with neurological deterioration and, in this case, increased the diagnosis suspicion. It is important to alert for similar cases and to reduce invasive diagnostic tests if the diagnosis is suspected.